The influence of short sprint performance, acceleration, and deceleration mechanical properties on change of direction ability in soccer players—A cross-sectional study - Zhang, Qingshan; Dellal, Alexandre; Chamari, Karim; Igonin, Pierre-Hugues; Martin, Cyril; Hautier, Christophe (Frontiers in Physiology, 2022)
The study investigated the relationship between short sprint performance and mechanical parameters obtained during the acceleration and deceleration tasks with the change of direction (COD) performance in female and male soccer players. The acceleration and deceleration ability were compared in the "High/Fast" versus "Low/Slow" COD performance group based on a median split analysis in each sex group. One hundred three French soccer players were assessed for the sprinting Force-Velocity (F-V) profile (i.e., theoretical maximal force [F0], velocity [V0], power [Pmax]), 10m performance, linear deceleration test (maximal braking force [HBFmax], braking power [BPmax], deceleration [Decmax]), and COD performance using 505-test. The 10m performance was strongly associated with 505-test performance (ES = [0.64 to 0.71]), whereas the sprinting F-V profiles parameters were weakly to moderately correlated with 505- performance (ES = [-0.47 to -0.38]). The BPmax was also moderately associated with 505-test performance (ES: range = [-0.55 to -0.46]). In addition, the High/Fast female COD group presented higher F0, Pmax, HBFmax, and BPmax than the Low/Slow group, whereas the male groups presented very few mechanical differences. Multiple regression analysis shows that the COD performance of male players was determined by 10m performance and maximum deceleration power. In contrast, no statistically significant model could be found to determine the change of direction performance in female players. In conclusion, the current finding indicated that the only variable strongly associated with COD performance was the linear 10m sprint time. In the same way, the mechanical parameters obtained from acceleration and deceleration seemed to play a non-neglectable role in this population.